THE BUSINESS TERMINOLOGY SUCH AS SPECIAL TERMS - Akramov, Bekzod Qahramonovich (Educational Research in Universal Sciences, 2022)
Terms and concepts organize the representation of the world and are part of relationships of contiguity, synonymy or even identity. Commercial job naming is no exception. But there is not one, but several terminologies. The company is the most representative witness to the evolution of terminology in this field, an evolution linked to the organization of the profession, the company and more generally society. Understanding the use, the motivation for the choice of these concepts, their dynamics, the type of relationship that unites them is a matter of socioterminology. Arriving at a consensual, non-reductive harmonization of concepts based on a field survey will lead to better knowledge sharing.